Electrocoating Polypyrrole on Gold-Wire Electrode as Potential Mediator Membrane Candidate for Anionic Surfactant Electrode Sensor - Abdul Haris Watoni; Indra Noviandri; Muhammad Nurdin; La Ode Ahmad Nur Ramadhan (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
The development of polypyrrole as a potential mediator membrane candidate for sodium dodecyl sulfate (SDS) sensor electrode has been investigated. The polypyrrole membrane was synthesized electrochemically from the pyrrole and coated at the surface of a 1.0 mm diameter of the gold-wire electrode. Electropolymerization of pyrrole and coating of the polypyrrole produced was performed by cyclic voltammetry technique in the electrochemical cell containing supporting electrolyte of 0.01 M NaClO4 with an optimum potential range of -0.9 V–1.0 V, the scanning rate of 100 mV/s, an electric current of 2 mA, and running of potential scanning of 10 cycles. By using the similar optimal parameters of cyclic voltammetry, electropolymerization of 0.01 M pyrrole solution containing 0.001 M SDS also produces a polypyrrole membrane coated at the gold-wire electrode surface. These coated electrodes have the potential response-ability toward DS- anions in the concentration range of 10-7 M–10-5 M with a limit of detection of 10-7 M and sensitivity of electrode of 9.9 mV/decade. This finding shows that the SDS solution’s role is as supporting electrolyte and also as a source of DS- dopant during the pyrrole electropolymerization processes. Dopants are trapped in the polymer membrane during the electrochemical formation of polypyrrole and role as ionophores for DS- anion in the analyte solution. A potential response to the electrode phenomena is excellent basic scientific information for further synthesis of conducting polymer and development of conducting polymer-coated wire electrode model, especially in the construction of ion-selective electrode (ISE) for the determination of anionic surfactants with those models.